ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGHADAPI TANTANGAN DIGITALISASI PENDIDIKAN DI SEKOLAH DASAR - Masithoh, Dewi; Hidayat, M. Rifdi (Mimbar Administrasi Mandiri, 2025)
The increasingly globalised development of science and technology represents a challenge in the digital era. The role of technology is expanding rapidly to support the learning process. It is therefore vital for education leaders to adapt to this changing landscape, adopt a leadership style that embraces technological innovation, and facilitate its effective integration into educational practices. This study aims to determine the principal's leadership style applied in the digital era in elementary schools. The study adopts a survey research design. The research was conducted from January to June 2024. The study's participants comprised class teachers and/or subject teachers, drawn from a population of elementary schools in Laren District, Lamongan, East Java. The research sample was obtained through the implementation of a simple random sampling technique, with a total of five elementary schools in Laren District, Lamongan, East Java, constituting the study's sample. Data collection techniques employed included the administration of questionnaires and guidelines. The data collection instrument employed was a questionnaire of a closed nature. The research data underwent a dual-stage analysis:Initially, a data validity test was conducted utilising the Person Product Moment correlation formula.Subsequently, a reliability test was performed employing the Cronbach Alpha formula. The statistical analysis of the score data was conducted using the software program Microsoft Excel. The results indicated that the principal's leadership style in addressing the challenges of the digital era can be categorised into five distinct styles: 1) transformational style with a percentage of 88.33%; 2) delegative style with a percentage of 87.78%; 3) transactional style with a percentage of 87.50%; 4) democratic style with a percentage of 86.25%; and 5) authoritarian style with a percentage of 85.17%. Of the five principal leadership styles, the most widely used and in accordance with the digitalization era is the transformational style, which demonstrates very strong criteria. The findings of this study are anticipated to furnish information that will inform policies on the utilisation of technology in the management of institutions at the elementary school level.